Proposing an Economic Justice Model in Iran's Budgeting System - Mohammad Soleimani, Manouchehr; Ameri Shahrabi, Mohsen; Shojaei Fard, Ali; Mohebbi, Serajuddin (Management Strategies and Engineering Sciences, 2026)
The aim of the present study is to propose a model of economic justice within Iran’s budgeting system. This research is applied in nature and utilizes a mixed-methods approach, combining qualitative and quantitative methodologies. In the qualitative phase, a causal analysis of the studied criteria was conducted through thematic analysis and expert interviews, leading to the development of a preliminary model. Subsequently, the quantitative phase was carried out through the design and distribution of structured questionnaires. The qualitative sample population consisted of 15 faculty members in the field of cultural management, selected through purposive sampling until theoretical saturation was achieved. In the quantitative phase, the sample size included 96 experts who were both accessible and willing to participate, selected through a combination of purposive (judgmental) and snowball non-probability sampling techniques. To analyze the model structure, grounded theory methodology was used, while structural equation modeling (SEM) was employed to assess the model's validity. The overall structure of the document analysis, carried out through in-depth interviews and using the MAXQDA software's document browser, revealed that the core variables of the study include enemy economy, resistance economy, financial discipline, corporate governance, commercial economy, and social economy. Three indicators were extracted for each of the six main variables. The results of the structural equation modeling demonstrated that the proposed model has a good fit.